Economics and politics of official loans versus grants: Panoramic issues and empirical evidence - Matthew Odedokun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The paper examines a wide range of issues relating to the mix between loans and grants as well as the degree of concessionality of loans. A number of empirical tests are carried out based on annual panel data over 1970 to 1999 for 22 donor countries and 72 recipient countries. Based on the tests, we are able to identify a number of economic and political factors that have influenced donors' past decisions on the grant-loan mix. We also observe that for bilateral donors, past grant-loan mix (and, hence, reflows from past transfers) do not influence the volume of current resource transfers. In addition, we find that loans are better suited than grants in promoting recipient governments budgetary discipline, as is commonly understood in fiscal reform literature. Our tests also show that the rate of official borrowing by the recipients (and, by deduction, the extent of their past debt burden) is positively influenced by the extent of the concessionality of such loans—irrespective of whether it is in the form of subsidized interest rates or longer grace periods. The paper concludes with a review of the circumstances in which grants, soft loans and non-concessional loans might have their respective comparative advantage, as well as a discussion of the need, so as to overcome the negative incentive problems of soft loans, for a typical concessional loan package to be separated into two constituent parts. This would enable the recipient to be given the grant component and the option to take from the non-concessional loan component as much as desired. – aid ; ODA ; grants ; official loans ; soft loans ; grant element ; grace period ; bilateral aid ; multilateral aid
Keywords: F34; F35; 330; Entwicklungshilfe